Oral Manifestations of T-Cell Large Granular Lymphocytic Leukemia: a Case Report - Ioanna-Eirini Arvanitidou; Nikolaos G. Nikitakis; Alexandra Sklavounou (eJournal of Oral Maxillofacial Research)
Background: T-cell large granular lymphocytic (T-LGL) leukemia is a rare, chronic, often indolent lymphoproliferative disorder of mature T cells (CD3+). Severe neutropenia and other cytopenias are common features in patients with T-LGL leukemia and may cause infections, thus representing a major cause of morbidity in this disease. Immunosuppressive therapy with low-dose regimes of methotrexate, cyclophosphamide, corticosteroids or cyclosporine A is the treatment of choice. Amongst the variety of T-LGL leukemia complications, oral manifestations such as ulcers have been rarely reported. The purpose of this paper is to report a case of T-cell large granular lymphocyte leukemia with oral manifestations and to discuss their pathogenesis and management.Methods: In the present case, a 65 year old female with a two-month history of diagnosed T-LGL leukemia presented with oral lesions, including ulcerations on the ventral tongue and soft palate as well as swollen, erythematous and ulcerated gingiva. The patient was under treatment with methotrexate, granulocyte colony-stimulating factor (G-CSF) and erythropoietin.Results: Considering patients’ medical history and clinical appearance of the lesions, a clinical diagnosis of a neutropenic ulcer of the tongue was established. The oral lesions resolved after treatment with antibiotics, topical steroids and antiseptics combined with improvement of the hematological condition. The pertinent literature related to T-LGL leukemia ethiopathology, diagnostics and treatment was discussed.Conclusions: Although rare, T-cell large granular lymphocytic leukemia should be included in the list of lymphoproliferative disorders, which may present with oral manifestations as a result of the disease and its treatment complications.